Slovakia - Technical Note on Consumer Protection in Financial Services : Volume 2 Sectoral Analyses and Good Practice Reviews - World Bank (Washington, DC, 2012)
As financial markets develop and deepen, one of the key issues for the fair, open and efficient operation of the markets is the protection of consumers rights in financial services. Be they bank depositors or borrowers or investors in insurance policies, securities or investment or pension funds, financial consumers need the ability to accurately understand the terms and conditions of their contracts and take action if the terms of contracts have been violated. The Note is the second report in a pilot program to analyze consumer protection in financialservices.The objectives of the Note are three-fold, to: (1) present a set of draft good practices for assessing consumer protection in financial services; (2) conduct a review of the existing rules and practices in Slovakia compared to the draft practices; and (3) provide recommendations on ways to improve consumer protection in financial services in Slovakia. The Technical Note wasprepared at the request of the Slovak Ministry of Finance, with the valuable support of the National Bank of Slovakia and other government agencies, ministries, and non-government organizations. In the past the World Bank has also prepared governance reviews of the Slovak financial sector for banking and private pension funds. Few guidelines are available for consumer protection in financial services. Consumer protection in financial services remains a new and developing area for which no consensus has developed on the broad parameters against which a specific country might be analyzed. This Note relied on the EU Directives related to consumer protection and the reports of European financialregulatory and supervisory agencies. Other sources were also used. In the United States, the Federal Trade Commission, the Securities and Exchange Commission and other state, federal and self-regulatory agencies have developed laws, rules and guidelines to protect financial consumers. In addition, the 2003 OECD Guidelines for Protecting Consumers from Fraudulent and DeceptiveCommercial Practices across Borders and the 1999 United Nations Guidelines for Consumer Protection served as useful reference points for general consumer protection not related to the financial sector. The recommendations in the Note go beyond the provisions of the EU Directives currently in force. As described in the EU Consumer Protection strategy announced in March 2007 and the April 2007 Green Paper on Retail Financial Services, European financial consumers wouldbenefit from stronger legal and institutional protections than are currently in place. Both in Europe and elsewhere, contemporary thinking on consumer protection is rapidly evolving. The Technical Note takes into account the international discussion on financial consumer protection and evolving good practices in financial consumer protection. Thus, the Note presents recommendations that are applicable to the Slovak financial sector, but in some cases go beyondthe minimum requirements set by EU legislation.